Kekuatan Hukum Letter C Sebagai Alat Bukti Hak Kepemilikan Atas Tanah - Fina Rohmatika; Malik Fahad; Sumriyah Sumriyah (Institut Nalanda, 2023)
Land is the most basic need for humanity since human life cannot exist apart from the soil. The Indonesian state is progressively seeing changes in the structure of land ownership rights, which is followed by the publication of land rules. Understanding of the early proof of ownership of land rights between the community and government entities in conflict zones,. Based on the legality of proof of ownership of legal property rights, namely a certificate, this creates a gap both vertically and horizontally, but in order to issue a certificate, it must be preceded by initial evidence of ownership such as letter C books, SPPT, and other evidence available at the village level, according to the Law. The Fifth Basic Agrarian Law of 1960. What is the strength of the evidence for quoting the village letter C book in gaining rights, and what is the method for obtaining land rights, and what is the status of ownership of land rights with proof of village letter C quotes.